Nimbuk Tradition of Dayak Deah Community in Mangkupum Village, Tabalong Regency during the Covid Pandemic - 19 Years 2019-2021 - Yemima Novitasari Bodoi; Fathimah Dayaning Pertiwi; Norhidayat Norhidayat (Yupa: Historical Studies Journal, 2025)
This study aims to explain how the implementation of the Nimbuk Ceremony tradition in Mangkupum Village, Tabalong Regency. The research method used is the Historical method which includes topic selection, heuristics, criticism, interpretation, and historiography. The focus of the research discusses the general description of Dayak Deah History and the implementation of the nimbuk ceremony. The Dayak Deah tribe is a Dayak sub-tribe that lives in an area located in Tabalong Regency, South Kalimantan which borders East Kalimantan. The Nimbuk Traditional Ritual is a ceremony carried out by the Dayak Deah community which aims to make a house for people who have died, the word Nimbuk comes from the Dayak Deah language. This Nimbuk ceremony is carried out by the community in groups and invites residents from other villages, held for 7 days. When covid19 occurred, the implementation of the Nimbuk Ceremony changed, during the covid-19 pandemic these activities were carried out with limited people and were more intimate. The community has an important role in preserving it, the community can socialize to the younger generation.